Prevalence and Morphological Characterization of Cheilospirura hamulosa, Diesing, 1861 (Nematoda: Acuarioidea), from Partridges in Iran - Maryam Ebrahimi; Soheila Rouhani; Iraj Mobedi; Ali Rostami; Hoshang Khazan; Mohammad Bagher Ahoo (Journal of Parasitology Research)
This study reports data on the prevalence, morphology, and morphometry of the nematode Cheilospirura hamulosa on the basis of light and stereoscopic microscopy and also camera lucida. Specimens were recovered after necropsies of 100 partridges (Alectoris chukar) from Taleqan County in Alborz Province, Iran. The prevalence of C. hamulosa in partridges was of 30% with a mean intensity of 3.9 and range of infection of 1–12. The mean length and width of females were 17.5±2.14 and 0.39±0.04 mm, while those of males were 12.2±0.67 and 0.3±0.06 mm, respectively. The characteristic digitiform tail was observed in females, and the unequal spicules, caudal alae, and ten pairs of caudal papillae were seen in males. The taxonomic characteristic longitudinal cordons and muscular and glandular oesophagus were observed in both sexes. Ratio between cordons and body length in males and females was 1 : 1.33 and 1 : 1.68, respectively. Ratio between long and short spicules in males was 1 : 2.3. The average size of embryonated eggs was 51.25×29.5 μm. In the present study, C. hamulosa (Nematoda: Acuarioidea) is recorded for the first time from partridges in Iran. Therefore, the morphological characters described in this study will be useful in the future diagnostic and taxonomic studies of Acuarioidea family.